The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/saj2.20275
|View full text |Cite
|
Sign up to set email alerts
|

Variable impact of compost on phosphorus dynamics in organic dryland soils following a one‐time application

Abstract: Prolonged benefits following a single application of compost in organic dryland wheat (Triticum aestivum L.) in the western United States have been documented, including the long-term bioavailability of phosphorus (P). Information on the bioavailability and forms of P following a one-time compost application in marginal organic agroecosystems with low and infrequent use of fertilizers is required to promote sustainability. The goal of this study was to evaluate changes in Hedley P pools following a one-time ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…However, the inhibition of oxidation enzymes (phenol oxidase and peroxidase) was noted. The authors suggest that adding N to soil stimulates microorganisms that produce a greater amount of enzymes that are associated with the hydrolytic acquisition of C. As reported by Li et al [100], statistical analysis showed that NT and C were the main predictors of AlP activity.…”
Section: Soil Enzyme Activitymentioning
confidence: 78%
See 2 more Smart Citations
“…However, the inhibition of oxidation enzymes (phenol oxidase and peroxidase) was noted. The authors suggest that adding N to soil stimulates microorganisms that produce a greater amount of enzymes that are associated with the hydrolytic acquisition of C. As reported by Li et al [100], statistical analysis showed that NT and C were the main predictors of AlP activity.…”
Section: Soil Enzyme Activitymentioning
confidence: 78%
“…This means that the rate of enzymatic release of phosphates from organic compounds is determined by the end product of several chemical reactions. Also, research by Li et al [100] showed that the activity of AlP, unlike AcP, explained the amount and dynamics of the content of available P in the soil. This suggests a different role of AlP in regulating P availability in soil long-term fertilised with FYM and N.…”
Section: Soil Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is confirmed by Sun et al [41], which showed a negative correlation between both APases and Olsen P and soil solution P. In this case, the negative association has been attributed to the hydrolysis of P compounds by other APase enzymes in the NaHCO 3 -extractable fraction, leading to an increase in dissolved inorganic P in the soil solution. However, other studies showed a positive association between APase activity (both ACP and ALP) and Olsen P, soil solution P, and organic P (Figure 3), which means that the dynamics of P fractions, particularly Olsen P, are closely related to plant development and can be influenced by climate and intrinsic soil characteristics [118,119]. Additionally, the addition of organic P sources, which increase the soluble P content, can negatively impact APase activity, as they contribute to the pool of available inorganic P in the soil [120].…”
Section: Phosphorusmentioning
confidence: 96%